Non‐Planar Perylene Bisimide Analogues with Inserted Carbonyl and Methylene Subunits. Issue 29 (11th June 2021) - Odajima, Mai; Tajima, Keita; Fukui, Norihito; Shinokubo, Hiroshi
Abstract: The synthesis and properties of dinaphthotropone bisimide (DNTrBI) and dinaphthocycloheptatriene bisimide (DNCHepBI) are described. Their molecular design is conceptually based on the insertion of a carbon atom into a perylene bisimide (PBI) core. These molecules adopt non‐planar structures due to the presence of a seven‐membered ring. The PBI derivative into which a carbonyl group was inserted (DNTrBI) immediately underwent nonradiative decay and/or intersystem crossing in its excited state. The PBI derivative into which a methylene group was inserted (DNCHepBI) was susceptible to deprotonation on account of the two electron‐withdrawing naphthalene monoimide units. Subsequent aerobic oxidation resulted in the formation of a C−C bond at the central methylene unit, thus affording a σ‐dimer. The formation of this C−C bond is dynamically redox‐active, i.e., electron injection into the σ‐dimer almost quantitatively regenerated the deprotonated DNCHepBI. Abstract : The synthesis and properties of perylene bisimide (PBI) analogues with an inserted carbonyl or methylene moiety are described. The carbonyl‐inserted PBI derivative immediately underwent intersystem crossing in its excited state. The deprotonation of the methylene‐inserted PBI derivative afforded the corresponding carbanion, which underwent redox‐induced reversible C−C bond formation to provide the corresponding σ‐dimer almost quantitatively.